RANCANGAN SISTEM INFORMASI DENGAN BALANCED SCORECARD UNTUK PENILAIAN KINERJA KOPERASI - Supriyati Supriyati; Mustafid Mustafid; Beta Noranita (Universitas Diponegoro, 2013)
Performance assessment in a company is needed to evaluate the progress in one year has passed in order to make an improvement in the next year. Balanced Scorecard Method (BSC) is one of performance assessment methods that measures 4 perspectives which are customer, financial, internal business process, also growth and learning perspective. In this research, performance assessment is measured by BSC method with 14 key personal indicators (KPI). Performance assessment is shown as assessment chart and target achievement graphic in every KPI for each perspective, also conclusion the conclusion of performance assessment that indicates the condition of the koperasi. Results of this research are in the form of web-based applications that is a part of information management system in koperasi. This system are giving information to all koperasi members about the performance update, so the members can give a suggestion to improve koperasi and their welfare also. Keywords : Balance Scorecard; Performance Assessment; KPI Koperasi